2022
DOI: 10.3389/fmicb.2022.904451
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Dominate the Cervical Immune Cell Population in Pregnancy and Their Transcriptome Correlates With the Microbial Vaginal Environment

Abstract: The cervicovaginal environment in pregnancy is proposed to influence risk of spontaneous preterm birth. The environment is shaped both by the resident microbiota and local inflammation driven by the host response (epithelia, immune cells and mucous). The contributions of the microbiota, metabolome and host defence peptides have been investigated, but less is known about the immune cell populations and how they may respond to the vaginal environment. Here we investigated the maternal immune cell populations at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Although, we had excluded the patients suffering the acute vulvovaginal candidiasis and bacterial vaginosis. Our finding supported the previous reports claiming neutrophils acted as the dominant immune cell type in the cervix [ 56 58 ]. The percentage of neutrophils was different with samples collected from biopsies [ 59 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although, we had excluded the patients suffering the acute vulvovaginal candidiasis and bacterial vaginosis. Our finding supported the previous reports claiming neutrophils acted as the dominant immune cell type in the cervix [ 56 58 ]. The percentage of neutrophils was different with samples collected from biopsies [ 59 ].…”
Section: Discussionsupporting
confidence: 93%
“…Evidence is emerging supporting the role of microbial-induced inflammation in modifying risk, with higher cervical-vaginal concentrations of cytokines such as IL-8, IL-6 and IL-1β and complement proteins C3b, C5 and C5a seen in association with in these high-risk vaginal microbial signatures [ 102 , 103 , 104 ]. It is plausible, that the predominant leukocyte influencing the local immune milieu is the neutrophil, with early studies beginning to support this [ 105 , 106 , 107 ].…”
Section: The Role Of Neutrophils In Preterm Labourmentioning
confidence: 99%
“…No statistically significant differences were seen in neutrophil concentrations between women who delivered preterm compared to at term, however the numbers of preterm deliveries were small (n = 18). Mohd Zaki et al have also reported that neutrophils are the predominant leukocyte population at the cervical-vaginal interface of women at high risk of preterm birth [ 105 ]. No significant differences were seen in neutrophil concentrations between women who delivered at term compared to preterm, however the study was likely to be underpowered for this outcome as only six women delivered preterm.…”
Section: The Role Of Neutrophils In Preterm Labourmentioning
confidence: 99%
“…Since TTV replication preferentially occurs in activated lymphoid cells (Brundin et al, 2020), and immune system activation is at its lowest level in case of a L. crispatus-dominated vaginal microbiome (Witkin and Linhares, 2017), we can speculate that the absence/decrease of TTV is linked to the reduction of lymphoid cells or their pro-inflammatory molecules when L. crispatus is predominant. On the contrary, the presence of L. iners is associated with a higher expression of genes involved in leukocyte mediated immunity and activation (Mohd Zaki et al, 2022), being potentially associated with higher levels of TTV in the vaginal environment.…”
Section: Discussionmentioning
confidence: 94%